1998
DOI: 10.1086/314509
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Polymorphisms in thePneumocystis cariniiCytochromebGene and Their Association with Atovaquone Prophylaxis Failure

Abstract: Atovaquone (Mepron, 566c80) is an effective agent against Pneumocystis carinii, which probably acts by binding to cytochrome b and inhibiting electron transport. To assess the possibility that atovaquone resistance might be developing, the genes for the cytochrome b from P. carinii sp. f. carinii and P. carinii sp. f. hominis were partially sequenced. Eight of 10 patient isolates had cytochrome b genes with the same amino acid sequence. The P. carinii cytochrome b genes from 2 of 4 patients who had atovaquone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
86
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 38 publications
3
86
0
Order By: Relevance
“…carinii sp. f. hominis has been suggested by the identification of isolates with polymorphisms in the gene encoding dihydropteroate synthase (DHPS), the target of sulphonamide drugs and in the gene encoding cytochrome b, the target of atovaquone [41]. The use of OP samples for sequence typing at these gene targets will greatly facilitate studies on the identification of drug resistance in l?…”
Section: Discussionmentioning
confidence: 99%
“…carinii sp. f. hominis has been suggested by the identification of isolates with polymorphisms in the gene encoding dihydropteroate synthase (DHPS), the target of sulphonamide drugs and in the gene encoding cytochrome b, the target of atovaquone [41]. The use of OP samples for sequence typing at these gene targets will greatly facilitate studies on the identification of drug resistance in l?…”
Section: Discussionmentioning
confidence: 99%
“…Because atovaquone is a valuable alternative drug for malaria, PcP, and toxoplasmosis, the development of drug-resistant populations is of serious concern (35,42,58,73). Increased cytochrome b mutations were detected in human-derived P. jirovecii from AIDS patients with prior exposure to atovaquone (35).…”
mentioning
confidence: 99%
“…This study showed that multiple mutations around the binding sites can lead to atovaquone resistance by decreasing the affinity for the drug by reducing the volume of the binding pocket. Atovaquone resistance may be more complex (73), as evidence is growing for multiple functions of CoQ (5,20,40,51,54,55,61,70) and its presence at cellular sites other than the mitochondrion.…”
mentioning
confidence: 99%
“…Basically, most fungi, e.g., Aspergillus nidulans, Neurospora crassa, Saccharomyces cerevisiae, and Schizosaccharomyces pombe, contain an intron(s) in their cyt b gene sequences (28). cyt b gene sequences of Pneumocystis carinii and C. glabrata do not contain introns (11,45). Among the 23 species of Trichosporon studied, 11 species had an intron(s) in the region sequenced.…”
Section: Discussionmentioning
confidence: 99%